Analysis of two-storey masonry structure under blast loading. (2023) - Raza, Ismail; Shamim, Saba; Ahmad, Shakeel; Khan, Rehan A.
Abstract: Masonry is the oldest and the most used building material but can suffer severe damage under the effect of blast load. Therefore, the present study focuses on investigating the blast response of two-storey masonry structure having varying areas of openings on the frontal wall. Four different numerical models: M1 having total opening area 2000 mm 2, M2 having total opening area 4000 mm 2, M3 having total opening area 8000 mm 2 and M4 having total opening area 12000 mm 2 were considered. The models have been developed in STAAD pro software using simplified macro-modelling approach. The blast load time history for 1000 kg explosive and standoff distance 15 m were developed using Indian standard. The nodal-force method was adopted and blast load was applied on each node of the finite element model. The results of the analysis were reported and compared in terms of major principal stress, minor principal stress and direct shear stress. The effect of opening area on blast response of masonry models was found to be quite significant.